The relationship between skin checking and sun protection behaviours: implications for skin cancer prevention campaigns. (February 2018) - Jongenelis, M.; Pettigrew, S.; Strickland, M.; Minto, C.; Slevin, T.
Highlights: Skin cancer is a highly prevalent yet preventable form of cancer. Sun protection public education campaigns achieved gains but results have plateaued. Increasing skin checking efficacy may increase checking and prevention behaviours.